Copolymerization of Epichlorohydrin and CO2 Using Zinc Glutarate: An Additional Application of ZnGA in Polycarbonate Synthesis. Issue 9 (15th March 2016) - Sudakar, Padmanaban; Sivanesan, Dharmalingam; Yoon, Sungho
Abstract : The use of zinc glutarate (ZnGA) as a heterogeneous catalyst for the copolymerization of epichlorohydrin, an epoxide with an electron‐withdrawing substituent, and CO2 is reported. This catalyst shows the highest selectivity (98%) for polycarbonate over the cyclic carbonate in epichlorohydrin/CO2 copolymerization under mild conditions. The (epichlorohydrin‐ co ‐CO2 ) polymer exhibits a high glass transition temperature ( T g ), 44 °C, which is the maximum T g value obtained for the (epichlorohydrin‐ co ‐CO2 ) polymer to date. Abstract : The ability of zinc glutarate (ZnGA) to produce polycarbonate from epichlorohydrin (ECH), an epoxide with an electron‐withdrawing substituent, and CO2 is revealed. This heterogeneous ZnGA catalyst shows highest selectivity (98%) for polycarbonate over the cyclic carbonate in ECH/CO2 copolymerization under mild conditions.